22 Traffic lights system a tool for paediatric inherited cardiac conditions patients produced by nurse specialists for patients and their families. (2nd February 2018) - Green, L; Casey, C
Abstract : Purpose: NHS England (2016) recognises that Early Warning Scores (EWS) aid identification of children at risk of clinical deterioration. NICE (2007) have strongly advised that EWS should be utilised for all inpatients. However, there is limited evidence to support the use of EWS within outpatient care for patients with chronic conditions. Literature recommends teaching patients symptom monitoring skills to recognise elevated heart failure risk. It is imperative that patients are able to identify signs of deterioration and seek appropriate help. Use of a symptom management tool can aid timely identification and management of symptoms, and access to relevant health services (Vincent and Mutsch, 2015). Methods: A Traffic Light System is being trialled within the Paediatric Inherited Cardiac Conditions (ICC) Service at Royal Brompton Hospital, developed with the view to act as a EWS for patients to use once discharged post inpatient care. It aims to; identify the severity of patient symptoms, relieve patient anxieties and support patients in taking appropriate actions in response to symptoms. Results: A questionnaire will be distributed to families who have used the tool, for the purposes of collecting and analysing data. This will assist in examining the effectiveness of the tool, and will ascertain whether or not it is beneficial for this patient group. Conclusion: Working with patients with chronic conditions involves a considerable amount of time supporting them with symptom advice and management. The Traffic Light System aims to empower patients to recognise symptoms, track them, identify early warning scores and for the patient/parents to act appropriately.